Penataan Pedestrian Berbasis Green Transportation di Politeknik Negeri Medan - Putri, Wirdatun Nafiah; Kusumadi, Kusumadi; Oktaviani, Tetra; Mabrur, Muhamad; Hani, Sheila (Universitas Methodist Indonesia, 2024)
In the UI Greenmetric assessment, transportation is one of the six categories that are required for a green campus, and one of the indicators is the pedestrian path on campus (TR8). In the transportation category, Medan State Polytechnic obtained a score of 725 or 40.3% of the total maximum value of the transportation category. The nonoptimal score obtained is due to the pedestrian path on campus indicator (TR8) obtaining one point with the availability of pedestrian. The addition of scores is made by pedestrian paths connected to all buildings designed for safety and convenience and in some parts provided with disabled-friendly features. It’s very important to have a pedestrian arrangement, to make Medan State Polytechnic become an environmentally friendly campus, which is the purpose of this research. The arrangement is making a pedestrian path layout that connects to the entire area of the Medan State Polytechnic Building and calculating the minimum width requirements of the pedestrian path, then making a pedestrian path layout. Pedestrian flow surveys were conducted on 5 pedestrians and 2 hallways that were considered representative of the pedestrian paths that available at Medan State Polytechnic. The results of calculations and adjusted by the provisions of the Ministry of Public Works and Public Housing 2023 on Pedestrian Technical Planning, the pedestrian path width requirement is 185 cm.